Anxiety and depression in adolescents with asthma: a study in clinical practice - Licari, Amelia; Castagnoli, Riccardo; Ciprandi, Riccardo; Brambilla, Ilaria; Guasti, Eleonora; Marseglia, Gian Luigi; Ciprandi, Giorgio (Acta Biomedica Atenei Parmensis, 2022)
Background: Anxiety and depression may affect asthma control. Previously, it has been reported that the hospital anxiety depression scale (HADS) questionnaire was fruitful in the management of adolescents with asthma. This study compared the scores of two different questionnaires, namely the Childhood Anxiety Sensitivity Index (CASI) and Children's Depression Inventory (CDI), with asthma control level and lung function in asthmatic adolescents, evaluated in a real-life setting.Methods: A group of adolescents with asthma was consecutively enrolled. Asthma was diagnosed according to the GINA document, and consistently the symptom control grade was assessed. The adolescents completed the CASI, CDI, and Asthma Control Test (ACT) questionnaires. Visual Analogue Scale (VAS) for asthma symptoms perception and doctor's asthma control evaluation were considered. Lung function and clinical characteristics were also assessed.Results: Totally, 87 asthmatic adolescents (60 males, 27 females, median age 14.2 years) were evaluated. 16.1% of asthmatic adolescents had anxious symptoms detected by CASI, and 11.5% depressive symptoms revealed by CDI. High scores of both CASI and CDI were significantly associated with uncontrolled asthma (p= 0.013 and 0.043, respectively).Conclusions: This study showed that anxiety and depression affected asthma control. Thus, in clinical practice, the psychological assessment could be included in asthmatic adolescents' asthma work-up.